2002
DOI: 10.1089/15209150252924175
|View full text |Cite
|
Sign up to set email alerts
|

Further User Comments Regarding Usage of an Interactive Educational Diabetes Simulator (AIDA)

Abstract: This "Diabetes Information Technology & WebWatch" column continues the diabetes simulation theme from previous issues and overviews various user experience with the AIDA v4 interactive educational freeware diabetes simulator. AIDA is a diabetes computer program that permits the interactive simulation of plasma insulin and blood glucose (BG) profiles for educational, demonstration, and self-learning purposes. It has been made freely available, without charge, via the Web as a noncommercial contribution to conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…This observation is also consistent with previously documented experience using the program with patients, [4][5][6] GPs, 2 and other health-carers. 7 In the current study, the majority of participants (n 5 23; 96%) reported finding AIDA promising as an educational tool and thought the software was useful (Table 1).…”
Section: Discussionsupporting
confidence: 91%
“…This observation is also consistent with previously documented experience using the program with patients, [4][5][6] GPs, 2 and other health-carers. 7 In the current study, the majority of participants (n 5 23; 96%) reported finding AIDA promising as an educational tool and thought the software was useful (Table 1).…”
Section: Discussionsupporting
confidence: 91%
“…While a large number of downloads of the AIDA software have been logged on the Internet, up to now, apart from user testimonials about the program 7,21,22 -and ad hoc comments received by the system developers via e-mail [23][24][25] -there has been little formal assessment as to who has actually been downloading or making use of the simulator, or more importantly, why.…”
Section: Discussionmentioning
confidence: 99%
“…While a large number of downloads of the software have been logged at the AIDA Website, up to now, apart from user testimonials about the program 4,27,28 and ad hoc comments received by the system developers via email, [29][30][31][32] there has been little formal assessment as to who has actually been downloading or making use of the simulator.…”
Section: Rationale For the Auditmentioning
confidence: 99%